A Population Survey on Barriers and Facilitators to Breast Cancer Screening Based on the Theoretical Domains Framework - Sarah Huf; Ada Humphrey; Ara Darzi; Deborah Cunningham; Dominic King; Gaby Judah (Behavioral Sciences)
Background: In the UK, breast cancer affects 1 in 8 women, accounting for 31% of cancers and 15% of cancer-related deaths in women. In 2023, London’s breast screening coverage was 56%, falling below the NHS target of 70%. This survey assesses psychological and behavioural factors impacting screening attendance. Methods: Using the Theoretical Domains Framework, an online survey including 15 behavioural factors was distributed through a market research company to women eligible for breast screening (aged 47–73) across London and Southeast and West England. Logistic regression was used to predict the impact of behavioural variables on history of attendance and intention to attend future screening opportunities. Results: Of the 922 respondents who returned the full survey, 88.6% intended to attend future screenings, and 88.1% reported previously attending screenings regularly. ‘Behavioural regulation’ had the strongest influence on past attendance (OR = 1.92, p < 0.001) and future intent (OR = 1.56, p = 0.003). Not intending to attend was linked to emotional consequences (OR = 0.68, p = 0.003) and environmental barriers (OR = 0.66, p < 0.001), where OR—Odds Ratio. Conclusions: This survey identifies behavioural factors influencing breast screening participation and screening intention, providing insights that may help design interventions to increase attendance rates.